دور الإتجاىات المعاصرة لإدارة التكلفة في دعم الميزة التنافسية بالمنشآت الصناعية دراسة ميدانية على شركة دال للصناعات الغذائية )كوكاكولا(: The Role of Contemporary Trends in Cost Management in Supporting the Competitive Advantage in Industrial Establishments A field study on Dal Company for Food Industries (Coca-Cola) - عبدالرحيم محجوب احمد محمد; ىارون آدم عيسى خميس; يحيى مقدم أحمد مارن; ياسر تاج السر محمد سند (Journal of North African Economies, 2025)
The study aimed to demonstrate the role of contemporary trends in cost management represented in: the target cost method, the activity-based cost method and the quality cost method in supporting the competitive advantage in industrial establishments. The problem of the study was to know how to support the competitive advantage of these establishments through the application of contemporary trends or methods for cost management, the analytical descriptive approach was used to analyze and describe the data of the study, and the questionnaire was used as a main tool in collecting field study data, the study reached several results that demonstrated the existence of a strong role for the contemporary trends of cost management mentioned in supporting the competitive advantage of industrial establishments.